Genetic correlation between multiple myeloma and chronic lymphocytic leukaemia provides evidence for shared aetiology - Went, Molly; Försti, Asta; Weinhold, Niels; Chen, Bowang; Bertsch, Uta; Hillengaß, Jens; Thomsen, Hauke; Goldschmidt, Hartmut; Hemminki, Kari (Blood cancer journal, 2019)
The clustering of different types of B-cell malignancies in families raises the possibility of shared aetiology. To examine this, we performed cross-trait linkage disequilibrium (LD)-score regression of multiple myeloma (MM) and chronic lymphocytic leukaemia (CLL) genome-wide association study (GWAS) data sets, totalling 11,734 cases and 29,468 controls. A significant genetic correlation between these two B-cell malignancies was shown (Rg = 0.4, P = 0.0046). Furthermore, four of the 45 known CLL risk loci were shown to associate with MM risk and five of the 23 known MM risk loci associate with CLL risk. By integrating eQTL, Hi-C and ChIP-seq data, we show that these pleiotropic risk loci are enriched for B-cell regulatory elements and implicate B-cell developmental genes. These data identify shared biological pathways influencing the development of CLL and, MM and further our understanding of the aetiological basis of these B-cell malignancies.
Published: 21 December 2018
Gesehen am 12.03.2020